Critical buckling load of honeycomb sandwich panels reinforced by three-phase orthotropic skins enhanced by carbon nanotubes. (1st April 2020) - Bacciocchi, Michele; Tarantino, Angelo Marcello
Abstract: The buckling analyses illustrated in this research aim to provide useful results for the design and application of sandwich plates with a honeycomb core and three-phase orthotropic skins, which are reinforced by both carbon nanotubes (CNTs) and straight oriented fibers. A multiscale approach is developed to this aim, which is based on the Eshelby-Mori-Tanaka scheme and the Hahn homogenization technique. The outcomes are presented in terms of critical buckling loads for different boundary conditions, lamination schemes, fiber orientation and mass fraction of CNTs, in order to prove that all these elements represent fundamental design parameters in the analysis, manufacturing and behavior of these sandwich plates. The theoretical framework is based on the Reissner-Mindlin theory for laminated plates and on the von Kármán hypothesis as far as the nonlinear terms are concerned. The kinematic model includes the Murakami's function to deal with such peculiar mechanical configurations, which is required to capture the zig-zag effect due to the different mechanical properties of the core and the external skins. The numerical approach and the theoretical methodology are validated by means of the comparison with the experimental and the theoretical results available in the literature.